A post-marketing safety assessment of COVID-19 mRNA vaccination for serious adverse outcomes using administrative claims data linked with vaccination registry in a city of Japan. Issue 52 (12th December 2022) - Takeuchi, Yoshinori; Iwagami, Masao; Ono, Sachiko; Michihata, Nobuaki; Uemura, Kohei; Yasunaga, Hideo
Abstract: Introduction: The safety profiles of COVID-19 vaccines are incompletely evaluated in Japan. Objectives: To examine the risk of serious adverse effects after COVID-19 mRNA vaccination (BNT162b2 and mRNA-1273) in cohort studies and self-controlled case series (SCCS). Methods: Using an administrative claims database linked with the COVID-19 vaccination registry in a city in Japan between September 2020 and September 2021, we identified health insurance enrolees aged ≥ 18 years. We evaluated the risk of acute myocardial infarction, appendicitis, Bell's palsy, convulsions/seizures, disseminated intravascular coagulation, immune thrombocytopenia, pulmonary embolism, haemorrhagic or ischemic stroke, venous thromboembolism, and all-cause mortality, 21 days following any COVID-19 mRNA vaccination, compared with non-vaccination periods. For the cohort studies, we estimated incidence rate ratios (IRRs) by Poisson regression and rate differences (IRDs) by weighted least-squares regression, adjusting for sex, age, and Charlson comorbidity index. We applied a modified SCCS design to appropriately treat outcome-dependent exposures. For the modified SCCS, we estimated within-subject IRRs by weighted conditional Poisson regression. Subgroup analyses stratified by sex and age were also conducted. Results: We identified 184, 491 enrolees [male: 87, 218; mean (standard deviation) age: 64.2 (19.5) years] with 136, 667 first and 127, 322 s dose vaccinations. The risks of any outcomes did not increase in any analyses, except for the fact that the modified SCCS indicated an increased risk of pulmonary embolism after the first dose in women (within-subject IRR [95%CI]: 3.97 [1.18–13.32]). Conclusion: The findings suggested that the COVID-19 mRNA vaccine was generally safe, whilst a signal of pulmonary embolism following the first dose of the COVID-19 mRNA vaccine was observed.